2014
DOI: 10.3345/kjp.2014.57.11.489
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and short-term outcomes of pediatric acute fulminant myocarditis in a single center

Abstract: PurposeThe aims of this study were to document our single-center experience with pediatric acute fulminant myocarditis (AFM) and to investigate its clinical features and short-term outcomes.MethodsWe performed a retrospective chart review of all children <18 years old who were diagnosed with AFM between October 2008 and February 2013. Data about patient demographics, initial symptoms, investigation results, management, and outcomes between survivors and nonsurvivors were collected.ResultsSeventeen of 21 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 25 publications
2
25
0
1
Order By: Relevance
“…However, if it progresses there is the risk of acute cardiac failure, hemodynamic disturbances, and arrhythmias leading to significant morbidity and mortality. Mortality due to myocarditis for infants is more than 75%, whereas for children it is more than 25% 1, 59 . There is no any specific clinical course and investigations to diagnose fulminant myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…However, if it progresses there is the risk of acute cardiac failure, hemodynamic disturbances, and arrhythmias leading to significant morbidity and mortality. Mortality due to myocarditis for infants is more than 75%, whereas for children it is more than 25% 1, 59 . There is no any specific clinical course and investigations to diagnose fulminant myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…The favorable outcomes associated with complete AVB in FM and AM were also reported. Lee et al (2014) reported the short-term outcomes of FM children in a single center and found that all seven FM children with complete AVB on the initial EKG survived. The AM patients with complete AVB perform excellent survival rates (89–100%) and long-term outcomes (100%).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the initial severe presentation, excellent short-term and long-term outcomes of FM with complete recovery of clinical manifestations and cardiac function have been found in the adult population (Felker et al, 2000; Ginsberg & Parrillo, 2013; McCarthy et al, 2000). While in the pediatric population, the outcomes of FM are controversial, with the mortality varied from 9.1% to 48.4% (Amabile et al, 2006; Saji et al, 2012; Lee et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Then, allergic reaction or autoimmune involvement can lead to further damage to cardiac muscle cells, resulting in localized or diffuse myocarditis. [5][6][7] The pathogenesis of anti-cardiac antibodies in post-viral autoimmune cases may start with direct viral-induced myocyte damage, with associated release of intracellular proteins.…”
mentioning
confidence: 99%